Design strategies to reduce surface water flooding in a historical district. (14th October 2016) - Lee, E.S.; Lee, D.K.; Kim, S.H.; Lee, K.C.
Abstract : Major causes of surface water flooding include increased surface water created by the expansion of impervious areas and increased localised heavy rains due to climate change. Older cities are vulnerable to surface water flooding because of their prior drainage systems. To identify vulnerable areas, this study applied an 'overlay method' using a geographic information system (GIS), which involved overlapping several spatial factors. The research area was the Gwanghwamun‐hyoja region – an old area of Korea that had surface flooding events in 2010 and 2011. Using a combination of Korean and Western flood‐management methods, this preliminary research suggests a design strategy for reducing surface water flooding and evaluates its efficacy. Five types of vulnerable areas are identified, and three types of design strategies are suggested. Using data from previous studies to simulate its effectiveness, the design strategy was found to reduce surface water by 33% after identifying the target area.